The gospel in the modern world a tribute to John Stott - Athyal, Saphir P.; Eden, Martyn, 1944-; Wells, David Falconer, 1939- (Leicester, UK IVP, 1991)
Includes bibliographical references.
Keywords: Stott, John Robert Walmsley, -- 1921- -- Theologian; Church and the world; Evangelicalism -- theology; Evangelistic work